Clinical characteristics of hepatocellular carcinoma patients with normal serum alpha‐fetoprotein level: A study of 112 consecutive cases. Issue 5 (26th October 2017) - Li, Li; Chen, Jinglong; Xu, Weiran; Ding, Xiaosheng; Wang, Xiangyi; Liang, Jun
Abstract: Background: Serum alpha‐fetoprotein (AFP) level is normal in 30–40% of hepatocellular carcinoma (HCC) patients, and knowledge on its characteristics and clinical outcome is limited. The purpose of this observational study was to determine the clinical presentation, biological behavior and outcome of HCC patients with normal AFP level. Methods: Data of 112 consecutive HCC patients with normal AFP level were analyzed retrospectively. Statistical analysis including survival and factors associated with serum AFP level were performed by Kaplan‐Meier method and t ‐test, respectively. Results: Hepatitis B virus infection exited in 83.0% of all 112 HCC patients with normal AFP level. During a mean 52 ± 20 months (range 5–85 months) follow‐up, the 1‐, 2‐, 3‐year overall survival (OS) rate was 97.2%, 85.3% and 81.7%, respectively. The OS rates at 3 years stratified by stages at diagnosis were 100%, 96.2%, 85.7%, 11.1% and 0%, respectively for Barcelona Clinic Liver Cancer (BCLC) stage 0–D diseases. Significant difference in OS was observed among patients with BCLC stage 0–D diseases, P < 0.05. Using 8.78 ng/mL as the cut off value, serum AFP level elevated beyond normal figure during follow‐up (AFP conversion) in 16 patients, which related with deterioration of liver function, quantitative changes of T helper cell subsets, rapid tumor progression and shorter survival. Patients with sustained normal AFP level had better survival than patients with AFP conversion, P < 0.05. There was significant difference between the time of diagnosis with HCC to serum AFP level elevation and the time of AFP elevation to death, P < 0.05. Conclusion: Prognosis of HCC patients with normal AFP level was relatively optimal. Serum AFP level elevation during follow‐up was significantly associated with clinical outcome in terms of OS.